2014
DOI: 10.1136/bjophthalmol-2013-304578
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy in patients with myopic macular retinoschisis

Abstract: PPV generally resulted in stable or improved VA for eyes with myopic macular retinoschisis. Eyes with concurrent macular hole or foveal retinal detachment often had improved VA, but to a lesser extent than eyes with myopic macular retinoschisis alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
11
0
1
Order By: Relevance
“…All patients were also examined by using new generation spectral-domain OCT. Preoperatively, OCT scans disclosed a marked increase in the thickness of the retina in the posterior pole area in all 13 eyes. As expected, the CFT was significantly reduced in all eyes postoperatively and this finding is also consistent with the previously published results [5,6,11,12,13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All patients were also examined by using new generation spectral-domain OCT. Preoperatively, OCT scans disclosed a marked increase in the thickness of the retina in the posterior pole area in all 13 eyes. As expected, the CFT was significantly reduced in all eyes postoperatively and this finding is also consistent with the previously published results [5,6,11,12,13].…”
Section: Discussionsupporting
confidence: 93%
“…In our case series, the mean BCVA improved from 20/80 to 20/50 after six months of surgery. Chang et al reported that the visual improvement was statistically significant from 20/130 to 20/70 in a retrospective study which has similar design with our study [13]. The visual gains are similar after surgery in both studies however, this study also includes the results of MF patients with macular hole, and thus the scores of preoperative and postoperative BCVA are lower than our study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Existing treatments are focusing on controlling the increase of the axial length and curing common complications [10,11]. Among them, surgical treatments include vitrectomy, internal limiting membrane removal, internal limiting membrane packing, posterior scleral reinforcement, and intravitreal injection of anti-vascular endothelial growth factor [12][13][14]. For example, for rhegmatogenous retinal detachment, one of the common complications of high myopia, intravitreal injection of exogenous lling is required in the reduction surgery for retinal detachment and posterior vitrectomy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…4). Mittels SD-OCT-Bildgebung ist es möglich, prognostische Faktoren für den funktionellen Erfolg nach MF-Chirurgie bei hoher Myopie zu finden [15][16][17]. Wachstum und zur Kontraktion der ERM [24,25].…”
unclassified